Decorative Features Of The Delphinium Plant - Nasritdinov Ahmadjon Abdukhamidovich; Yuldasheva Jasmina Rasuljonovna. (Zien Journals, 2024)
In recent years, environmental protection, landscaping of populated areas, adaptation of new trees, shrubs and flowers to local conditions have become an important issue. This delphinium is a beautiful ornamental flower plant of white, red, pink and purple colors. They are important for landscaping alleys, districts, parks and creating a landscape image
Keywords: delphinium plant; tree-shrub; flowers; hollow stem